2019
DOI: 10.1029/2018je005699
|View full text |Cite
|
Sign up to set email alerts
|

A Global Inventory of Ice‐Related Morphological Features on Dwarf Planet Ceres: Implications for the Evolution and Current State of the Cryosphere

Abstract: We present a comprehensive global catalog of the geomorphological features with clear or potential relevance to subsurface ice identified during the Dawn spacecraft's primary and first extended missions at Ceres. We define eight broad feature classes and describe analyses supporting their genetic links to subsurface ice. These classes include relaxed craters; central pit craters; large domes; small mounds; lobate landslides and ejecta; pitted materials; depressions and scarps; and fractures, grooves, and chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 127 publications
(353 reference statements)
7
45
0
Order By: Relevance
“…Special circumstances, such as a local ice layer that extends closer to the surface (e.g., at Juling and in the high latitudes) or deep excavation by impacts (in the case of contact craters) could then allow for deeper failure or anomalous landslide mobility, producing what we observe as “outlier” behavior relative to the majority of landslides. Coupled with the concurrence of landslides with surface ice (Combe et al, ) and other morphological features associated with ice (fluidized ejecta, pitted materials, and small‐scale fractures; Sizemore et al, ) near Kupalo and Juling craters and near Urvara crater, our analysis is consistent with the conclusion that these regions possess particularly high ice content. Clusters of landslides and other ground ice‐related features that tentatively extend from Juling, Kupalo, and Urvara through the Hanami Planum could be consistent with ice‐rich highlands and thus offer a potential target for future studies of crustal ice content.…”
Section: Discussionsupporting
confidence: 87%
“…Special circumstances, such as a local ice layer that extends closer to the surface (e.g., at Juling and in the high latitudes) or deep excavation by impacts (in the case of contact craters) could then allow for deeper failure or anomalous landslide mobility, producing what we observe as “outlier” behavior relative to the majority of landslides. Coupled with the concurrence of landslides with surface ice (Combe et al, ) and other morphological features associated with ice (fluidized ejecta, pitted materials, and small‐scale fractures; Sizemore et al, ) near Kupalo and Juling craters and near Urvara crater, our analysis is consistent with the conclusion that these regions possess particularly high ice content. Clusters of landslides and other ground ice‐related features that tentatively extend from Juling, Kupalo, and Urvara through the Hanami Planum could be consistent with ice‐rich highlands and thus offer a potential target for future studies of crustal ice content.…”
Section: Discussionsupporting
confidence: 87%
“…We estimate an upper bound of~30 vol.% mechanically silicate-like phases within the mechanical layer at Nar Sulcus, which is broadly consistent with Fu et al's (2017) and Ermakov et al's (2017) estimate of the global rock volume fraction within the upper layer of Ceres. This result is consistent with the variations in ice content in Sizemore et al (2018) with more ice observed in association with large craters and basins. This result is consistent with the variations in ice content in Sizemore et al (2018) with more ice observed in association with large craters and basins.…”
Section: Geophysical Research Letterssupporting
confidence: 90%
“…Their morphology and evolution are directly influenced by the properties of Ceres' upper layers, which seem to be composed of relatively mechanically strong constituents (Russell et al, ), such as a silicate‐rich rock‐ice mixture containing salt and clathrate hydrates, carbonates (Bland et al, ; De Sanctis et al, , ; Fu et al, ), and ammoniated phyllosilicates (De Sanctis et al, , Ammannito et al, ). However, there are a number of features suggesting the presence of water ice in Ceres' upper layers (Sizemore et al, ), such as lobate landslides (Schmidt et al, ), domical features (Ruesch et al, ), pitted terrains (Sizemore et al, ), and smooth long‐wavelength topography (Fu et al, ). The shallow subsurface may contain a maximum of 30–40% water ice by volume on average, although there is evidence of regional heterogeneity (Bland et al, ; Fu et al, ).…”
Section: Introductionmentioning
confidence: 99%